Mechanical and microstructure analysis of copper to copper foam brazing using copper-tin nickel-phosphorus amorphous filler alloys / Nur Amirah Mohd Zahri - Nur Amirah , Mohd Zahri (2021)
Heat exchangers made with metal foams elements have great potential in thermal applications as they have high heat flux cooling due to their large surface to volume ratio. However, finding an effective joining method to incorporate metal foams into heat exchanger designs is very challenging and has become a topic of interest in brazing technology. In this study, the brazing of copper foam to solid copper using different copper-tin-nickel-phosphorus (Cu-Sn-Ni-P) amorphous filler alloys was investigated. The parameters evaluated included the pore densities of Cu foams (pore per inch- PPI), the fillers metal and the brazing temperatures. The resultant joints were evaluated for compressive and shear strengths to determine their mechanical reliabilities. Microstructural evaluations were conducted on the brazed interface using Scanning electron microscope (SEM), X-ray diffraction (XRD) and Energy-dispersive X-ray spectroscopy (EDX) (point, line and area mapping). Finally, the corrosion behaviours of crystalline filler alloys and Cu/Cu foam/Cu brazed joints were analysed using electrochemical potentiodynamic polarisation and immersion tests, respectively. It was found that the compressive strengths of brazed Cu/Cu foam/Cu increase with increasing foam pore density. The highest compressive strength of 14.4 MPa was obtained for 50 PPI Cu foam brazed sample followed 25 PPI and 15 PPI Cu foams. This increase in compressive strength was due to the dense interconnected branches in 50 PPI Cu foam. In contrast, the highest shear strength of 3.7 MPa was obtained for brazed joint sample of 15 PPI Cu foam as compared to 25 PPI (3.3 MPa) and 50 PPI (2.8 MPa) Cu foams. This was due to the larger area of interconnected branches in 15 PPI Cu foam. SEM images revealed increases in cavities formation in the joint interface with increasing Cu foam pore density which correspond with the decrease in brazing joint strengths. EDX and XRD analysis have shown the concentrations of Cu, Cu6Sn5, Cu3P and Ni3P in the joint. EDX line scanning has verified the diffusion of P element into the Cu foam, which would have strengthened the Cu foam branches and contribute to its high compressive strength properties. The electrochemical potentiodynamic polarisation tests have shown that the Cu-9.7Sn-5.7Ni-7.0P filler has less noble corrosion potential (Ecorr) which make it prone to corrosion attack. However, Cu-9.7Sn-5.7Ni-7.0P filler has a more negative of corrosion current density (Icorr), indicating low corrosion rate and high corrosion resistance. This observation agrees with the immersion test of Cu/Cu foam/Cu using Cu-9.7Sn-5.7Ni-7.0P filler, which resulted in the thickest patina layer formation (initially formed by an aggressive corrosion) protecting the interface from further corrosion attack (high corrosion resistant). By considering the aspect of manufacturing, Cu foam strength, brazed joint strength, microstructure and corrosion performance, it is proposed that Cu/Cu foam /Cu with 15 PPI Cu foam using Cu-9.7Sn-5.7Ni-7.0P filler at brazing temperature of 680 °C would be the most suitable configuration for use in heat exchanger applications.